Restorative model: The alternative justice response to the victims of sexual violence - Mohamad Yunus, Mohamad Ismail (Faculty of Law, Lampung University, Indonesia, 2017)
Adversarial justice system seems to focus on punishing the sexual offender without adequately repositioning sexual crimes victims. There is the need to redefine the role of sexual crime victims by giving them a voice in outcome of judicial process through alternative justice models. Although the Criminal Procedure Code recognises the discretionary powers of the court to grant compensation, the court order the offenders to pay restitution to the victim. This article seeks to examine the victim compensation under criminal justice administration and recommend a legal framework for alternative justice models for sexual crimes offences. The article will recommend mechanisms for alternative justice suitable for the administration of justice in Malaysia. The alternative justice response is restorative justice, model which will give effect through compensation or restitution. It is also proposed for the establishment of the Victim Compensation Scheme (VCS) to be set up and administered under the Malaysian Criminal Procedure Code.